2017
DOI: 10.1111/1471-0307.12459
|View full text |Cite
|
Sign up to set email alerts
|

Textural and microstructural properties of Kradi cheese (an indigenous cheese of Jammu and Kashmir, India)

Abstract: The texture and microstructure of Kradi cheese, an indigenous fresh unripened cheese of Jammu and Kashmir, India, were studied. There were significant differences (P < 0.05) for hardness, adhesiveness, springiness, cohesiveness, chewiness and resilience between samples from four different market areas. The optimised products made in the laboratory from cultures NCDC‐167 and NCDC‐144 showed significant differences (P < 0.05) in the textural and mechanical properties of tensile strength. The microstructure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Studies on the physicochemical properties and characteristics of various cheeses have recently been conducted. Matera et al (2018) studied the physicochemical characteristics of Brazilian cheeses Salum et al (2019) the compositional properties of enzyme-modified commercial cheeses, Punoo et al (2018) the textural and microstructural properties of Kradi cheese and Rafiq et al (2018) cheddar cheese peptide extracts in anticancer activity. Researches related to Prato cheese include the partial replacement of NaCl by KCl and the addition of flavor enhancers to the probiotic Prato cheese (Silva et al, 2018), the change in volatile compound concentration during the maturation of Prato cheese by reducing fat and adding whey protein (Domingos et al, 2019), and attenuation of cigarette smoke-induced lesions in mice by the probiotic Prato cheese (Vasconcelos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the physicochemical properties and characteristics of various cheeses have recently been conducted. Matera et al (2018) studied the physicochemical characteristics of Brazilian cheeses Salum et al (2019) the compositional properties of enzyme-modified commercial cheeses, Punoo et al (2018) the textural and microstructural properties of Kradi cheese and Rafiq et al (2018) cheddar cheese peptide extracts in anticancer activity. Researches related to Prato cheese include the partial replacement of NaCl by KCl and the addition of flavor enhancers to the probiotic Prato cheese (Silva et al, 2018), the change in volatile compound concentration during the maturation of Prato cheese by reducing fat and adding whey protein (Domingos et al, 2019), and attenuation of cigarette smoke-induced lesions in mice by the probiotic Prato cheese (Vasconcelos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of Kradi cheese Kradi cheese was made as per the method described (Punoo et al 2018a). The fresh product was packed in multilayer laminates (5-layer natural PFP, 20x20 cm size and 105-175 micron thickness of film) under vacuum and normal packaging conditions and stored at refrigeration temperature (5±1 o C).…”
Section: Methodsmentioning
confidence: 99%
“…Kradi, semisoft, white, unripened fresh cheese (Punoo et al 2018a(Punoo et al , 2018b(Punoo et al and 2018c) is a famous traditional milk product of Jammu and Kashmir, India manufactured primarily by the tribal population of Gujjar and Bakarwal community. It is sold unpackaged, undergoes moisture loss and increase in acidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kradi cheese is usually stored at different temperatures by the retailer for sale, there is need to study effect of packaging conditions on chewiness of product with an aim to improve the overall quality of the product so that the product remains acceptable to consumers with respect to quality. Physico chemical, microbiological, microstructural properties, descriptive sensory analysis and chemical changes during storage of kradi cheese have been reported [9,10,13,12]. Since chewiness is important textural quality judged by consumer at the time of purchasing the kradi cheese, however no studies have been reported with respect to changes in chewiness of kradi cheese during storage.…”
Section: Introductionmentioning
confidence: 99%